Eighteenth-century Scientific Racism and Self-representation Strategies: Olaudah Equiano’s Interesting Narrative - Gallego Durán, Mar (Estudios Ingleses de la Universidad Complutense, 2011)
Olaudah Equiano’s Interesting Narrative is presented as an excellent reference for slave narratives, as it responds to the controversial image of Africans as inferior beings fostered by the incipient scientific racism in the eighteenth-century, while simultaneously developing significant selfrepresentation strategies. To analyze the narrative, attention will be focused on three main aspects: firstly, the way in which the sustained attack on the slavery institution dismantles the myths and legends promoted by racist ideology based on scientific racism’s tenets; secondly, the use of religious discourse as one of the most influential discourses to substantiate pro-abolition arguments; and thirdly, the fashioning of a series of rhetorical strategies that facilitate the construction of a fluid and multirracial narrative self.